Combining PBL and CLIL in the scientific laboratory in secondary education - Álvarez-Sánchez, Beatriz (My University, 2016)
Several connections can be made between the principles of CLIL methodology and the practical dimension of lab experiments. Thus, science lab offers a unique scenario for learning by doing, active learning, collaborative tasks and language use in a real context. In addition, the scientific laboratory represents a very flexible learning environment with regards to the activities that can be performed although there are no precedents of applying CLIL in lab experiments. In this research proposal, different approaches such as project-based learning (PBL), inquiry-based learning (IBL), or task-based learning (TBL), have been used in the implementation of CLIL in the scientific laboratory for learning purposes. As a result, we propose PBL as a feasible approach to implement CLIL in the scientific laboratory as it provides the learning by doing dimension while introducing inquiry and problem solving in cognitively demanding tasks. With this aim, a methodology for effective planning PBL from a CLIL perspective is here proposed. This planning has been developed from a practical point of view, considering aspects related to lab work (i.e. safety considerations), CLIL methodology (i.e. using the 4Cs framework as a starting point to integrate language and content from a holistic view) and defining aspects of PBL (i.e. the creation of artifacts as a creative culmination of the project, or the generation of a driving question as the guiding force of projects). After outlining the main aspects of CLIL-based PBL applied to scientific experiments, the expected outcomes and possible pitfalls have also been considered. The integration of project-based learning and CLIL in the scientific laboratory is expected to connect with students‘ needs and interests through their active role in the learning process and the real world connection of scientific projects. In addition, it should engage them in cognitively demanding tasks, while using the language in a purposeful and meaningful context, thus impacting in their lifelong learning.
Keywords: project-based learning; PBL; science teaching; Content and Language Integrated Learning; CLIL and science laboratory; Máster Universitario en Educación Bilingüe